Pilot and Feasibility of Combining a Medication Adherence Intervention and Group Diabetes Education for Patients with Type-2 Diabetes - Matthew Witry; Melissa Ernzen; Anthony Pape; Brahmendra Reddy Viyyuri (MDPI AG, 2019)
Introduction: Controlling diabetes typically requires self-management and medications. Community pharmacists are positioned to support patients with both. Methods: This study assessed the feasibility and potential benefit of combining pharmacist-provided group diabetes education (up to eight sessions) and medication synchronization using a three-group design. Data were collected using pre−post paper surveys and electronic health record data. One group received both education and synchronization services, another group received medication synchronization only, and a third served as control. Results: Of 300 contacted patients, eighteen patients participated in group diabetes education, 14 had medication synchronization only, and 12 comprised a control group. There was little change in HbA1c over the study period. Medication adherence appeared to be positively aided by medication synchronization, although all groups started with high adherence. Some medication beliefs and self-care activities may have been positively impacted by group diabetes education. Both groups receiving medication synchronization were satisfied. Conclusions: Participants strongly agreed they would recommend group diabetes education from the study pharmacy to a friend and were satisfied with medication synchronization; however, it was difficult to tell if there was a synergistic effect by combining the two services. Reimbursement for diabetes education was not obtained despite multiple attempts, hindering sustainability.